68 National sarcoma MDT reform: the art of kintsugi. A quality improvement project to the direction of optimal person – centred care. (3rd November 2019) - Watson-Fargie, T; Lo, S; Cowie, F; White, J; Chong, P; Mahendra, A; Campbell, L; Paterson, C; Nixon, I
Abstract : Introduction: Sarcomas are rare and diverse malignancies, constituting of <1% of all cancers. The National Sarcoma Multidisciplinary Team Meeting has a pivotal role in the management of sarcoma patients and it functions to enable safe, timely, equitable, person-centred care. Previous audit work showed 17% of cases referred for discussion at the National Sarcoma MDT are deferred due to lack of information. Recently a new robust referral process and a new referral form was implemented to improve the quality of referrals received. Aims: To increase the percentage of referred cases that are discussed by improving quality of the referral process. Methods: Data was collected over two data periods during different phases in implementation of a new referral process. PDSA cycles were performed and data compiled into a Microsoft Excel document for analysis. Results: Implementation and encouragement of a new referral form showed an increase in the key domains of information required for MDT discussion. This resulted in an increase in case discussion by 15%. Conclusion: Referrals to a national MDT need to be succinct yet provide key clinical information to allow for adequate discussion and management. Implementation of a rigorous referral process will improve patient care in this setting and highlighting form adherence has improved its completion.